Near‐visible stereolithography of a low shrinkage cationic/free‐radical photopolymer blend and its nanocomposite. Issue 5 (2nd August 2019) - Invernizzi, Marta; Suriano, Raffaella; Muscatello, Allegra; Turri, Stefano; Levi, Marinella
ABSTRACT: In this work, a newly prepared cationic/free‐radical photopolymer, which consists of two epoxies and a tetrafunctional acrylate, is presented for the first time for a visible light stereolithography (SL), showing the advantages of both cationic and free‐radical resins. An onium salt, commonly used as a cationic UV initiator, and a photosensitizer make the blend suitable for a near‐visible (405 nm) SL. An increase in the polymerization rate and a drop in the induction period are observed for the newly prepared cationic/free‐radical blend, compared with either only cationic systems or free‐radical resins. This suggests that the combination of cationic and free‐radical polymerizations in a single resin has a positive synergistic effect. The addition of silica nanoparticles to the blend provides a reinforcing and toughening effect. Indeed, the resin loaded with silica shows a 31% increase in the elastic modulus, compared with the unfilled resin. Regarding the values of tensile strength and elongation at break, they, respectively, grow by 47 and 15%, when the nanocomposite resin is compared with the neat resin. A very low volumetric shrinkage of 0.7% and a remarkable printing quality of objects obtained with this new photopolymer will enable the 3D printing of microrobots, bioengineering microdevices, and sensors. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48333. Abstract :